Gambaran entrepreneurial passion pada wanita pengusaha milenial Kota Bukittinggi - Irsal, Fitria Nadhila; Putra, Yanladila Yeltas (Universitas Negeri Padang, 2023)
This research aims to understand the representations of entrepreneurial passion among millennial women entrepreneurs in Bukittinggi City. By understanding the entrepreneurial passion, an entrepreneur, especially a women entrepreneur, can understand the important role of passion in starting and maintaining business activities. In an effort to achieve the research objectives, a qualitative research with a phenomenological approach was carried out on participants selected purposively, namely millennial women entrepreneurs. Data collection techniques were carried out by interviews. Data were analyzed and validated according to techniques developed by Miles and Huberman. The results of this research are that the entrepreneurial passion of millennial women entrepreneurs is reflected in three aspects of entrepreneurship in the form of efforts to create, establish and develop a business. Apart from that, the research results are also supported by psychological aspects which also play a role in depicting entrepreneurial passion.